Assessment of nutritional status in adolescent girls residing in social welfare hostels in Tirupati town: a cross sectional study - Deekala, Ravi Sankar; Kokku, Meghana Reddy (International Journal Of Community Medicine And Public Health, 2018)
Background: One way to break the intergenerational cycle of malnutrition is to improve the nutrition of adolescent girls prior to conception. Adolescent health and nutrition are important issues which have not received the attention it deserves in our country, especially in the context of a girl child. The objectives of the study were to assess the nutritional status of the adolescent girls residing in the social welfare hostels of Tirupati town, Andhra Pradesh. Methods: The Nutritional status will be assessed by anthropometric measurements (i.e., height, weight, BMI) and questionnaire. Results: 54.1% of the adolescent girls were underweight.61.4% of them studying 1st and 2nd years of their graduation. 52.2% of them belonged to upper lower class according to modified Kuppuswamy classification 2016.76% of adolescent girls belonged to the family size of less than or equal to five. 44.1% has one sibling. 33% of the adolescent girls use nutritional supplements.59.7% of adolescent girls has junk food once a week. 56.1% of them routinely involve in moderate physical activity. 4.1% of them who attained menarche do not practice menstrual hygiene. 62.3% of them visited health center for 1-5 times in the past one year.71.5% of them does not practice deworming. 5.9% observed worms in their fecal matter. 19.7% of the adolescent girls have vision problems. 67.3% of adolescent girls have awareness regarding nutritional health. Only 28.2% of adolescent girls get cosmetic charges from government. Conclusions: There is relation between nutritional status and educational level (better among graduates).